2019
DOI: 10.1002/ange.201911617
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Superhydrophilic/Superaerophobic Electrocatalyst Composed of the Supported CoMoSx Chalcogel for Overall Water Splitting

Abstract: The development of high-efficiency electrocatalysts for large-scale water splitting is critical but also challenging.In this study,ahierarchical CoMoS x chalcogel was synthesized on anickel foam (NF) through an in situ metathesis reaction and demonstrated excellent activity and stability in the electrocatalytic hydrogen evolution reaction and oxygen evolution reaction in alkaline media. The high catalytic activity could be ascribed to the abundant active sites/defects in the amorphous framework and promotion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Liu et al reported a hierarchical CoMoSx chalcogel on a Ni foam synthesized through an in-situ metathesis reaction. This electrocatalyst realized a current density of 100 mA•cm −2 below 1.74 V, which is lower than that of MoSx without Co doping (1.87 V) [20]. Dong et al prepared Co-doped β-molybdenum carbide (β-Mo2C) encapsulated by a N-doped carbon framework, which afforded a current density of 10 mA•cm −2 for the OER at a low overpotential of 1.6 V and provided a significant improvement in performance over β-Mo2C (over 1.8 V) [21].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Liu et al reported a hierarchical CoMoSx chalcogel on a Ni foam synthesized through an in-situ metathesis reaction. This electrocatalyst realized a current density of 100 mA•cm −2 below 1.74 V, which is lower than that of MoSx without Co doping (1.87 V) [20]. Dong et al prepared Co-doped β-molybdenum carbide (β-Mo2C) encapsulated by a N-doped carbon framework, which afforded a current density of 10 mA•cm −2 for the OER at a low overpotential of 1.6 V and provided a significant improvement in performance over β-Mo2C (over 1.8 V) [21].…”
Section: Introductionmentioning
confidence: 74%
“…In the next step, a solution-phase method [20] was employed to produce the Co-doped NiMoO4 precursor ((NiMo)1−xCoxO4/NF) with an estimated Co content of ~ 1 wt.%, as determined by semi-qualitative elemental mapping (Fig. S3 in the ESM).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctive features of transition‐metal sulfide (TMS x ) chalcogel materials, including large porosity, extensive surface area, and exceptional electrochemical properties, have recently captured the attention of researchers in the field of catalysis. Several noteworthy studies have reported significant improvements in the catalytic performance and stability using TMS x chalcogels such as 40% GO/CoMo 3 S 13 , CoMoS x , and CoMoS x /nickel foam (NF) chalcogels 93,284,285 . Moreover, recent research has focused on understanding the gas–liquid–solid three‐phase interfaces in CoMoS x chalcogels on NF, which suggest that TMS x chalcogels can be promising materials for electrochemical catalysts 285 …”
Section: Metal‐chalcogenide–derived Aerogel (Chalcogel)mentioning
confidence: 99%
“…Several noteworthy studies have reported significant improvements in the catalytic performance and stability using TMS x chalcogels such as 40% GO/CoMo 3 S 13 , CoMoS x , and CoMoS x /nickel foam (NF) chalcogels 93,284,285 . Moreover, recent research has focused on understanding the gas–liquid–solid three‐phase interfaces in CoMoS x chalcogels on NF, which suggest that TMS x chalcogels can be promising materials for electrochemical catalysts 285 …”
Section: Metal‐chalcogenide–derived Aerogel (Chalcogel)mentioning
confidence: 99%